help your girl out !!
![help your girl out class=](https://us-static.z-dn.net/files/d4a/31c41a44f5e46a9bcfe269374487232e.png)
(5x² - 6x + 2)(4x² - 3x)
[tex]20x^{4} -15x^{3} -24x^{3} +18x^{2} +8x^{2} -6x[/tex]
[tex]20x^{4} -39x^{3} +26x^{2}-6x[/tex]
Your answer is A
A
multiply each term in 5x² - 6x + 2 by each term in 4x² - 3x, as shown below
4x²(5x² - 6x + 2 ) - 3x(5x² - 6x + 2 ) ← distribute
=20[tex]x^{4}[/tex] - 24x³ + 8x² - 15x³ + 18x² - 6x ← collect like terms
= 20[tex]x^{4}[/tex] - 39x³ + 26x² - 6x → A